Formic acid-sulfide synergistic aging kinetics and nanometer titanium dioxide modification mechanism in oil-immersed transformer insulation system - Yuedong Gao; Zhangcheng Li; Peng Cheng; Yue Zhang; Xiao Wei; Pengfei Jia (PLoS ONE, 2026)
This study investigates the synergistic aging effects of formic acid and sulfides on oil-immersed transformer insulation systems and explores the mitigating role of titanium dioxide (TiO₂) nanoparticles. A series of multi-factor coupled accelerated aging experiments were conducted under controlled ambient conditions (25 ± 3 °C) to monitor the mechanical strength of insulating paper and the dielectric breakdown voltage of insulating oil. Results show that formic acid is the dominant agent in early-stage degradation, causing a sharp 63.88% drop in tensile strength within 30 days due to catalytic hydrolysis, followed by partial recovery to 50% of the initial value through crosslinking of degradation products. Notably, the coexistence of formic acid and powdered sulfur causes severe synergistic corrosion, leading to an 82.3% strength reduction and a dramatic decline in breakdown voltage to 7.2 kV. Conversely, the formic acid–DBDS system exhibits a protective synergy, with tensile strength and breakdown voltage recovering to 206 kN/m and 30.2 kV, respectively. The introduction of nano-TiO₂ enhances these effects, especially in DBDS environments, by forming passivation layers and interfacial traps that suppress degradation. These findings provide insights into the nonlinear coupling of chemical corrosion, interfacial modification, and insulation performance evolution in transformer systems.